(untitled) (Applied Biological Research, 2015)
Cumin (Cuminum cyminum Linn.), an important commercial seed spice with medicinal properties, belongs to family Umbelliferae. The present study was aimed to elucidate the high quality 3D structure and function of cumin protein (gn50). For the prediction of secondary structure of proteinFASTAsequenceswere used and prediction was performed using GOR IV, SOPMA, ProFunc and PDBSum. The instability index 24.29, isoelectric point (pI) 5.14 and Grand average hydropathicity (GRAVY) 0.751 determined from primary and secondary structural analysis illustrated the stability of cumin protein. Stability of 3D structure of protein was confirmed using Ramachandran plot having 80.1% residues or empirically distributed data-points present in the structure lie in most favoured region with the total score of 98.3%. The models were validated using protein structure checking server SAVES.